2019
DOI: 10.3390/su11185125
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Innovation Impact on Recycling Municipal Waste. A Panel Data Analysis at the EU Level

Abstract: Based on recent findings of the economic literature on the implications of entrepreneurial innovation for recycling municipal waste, this paper aims to examine the main factors of recycling municipal waste at the European Union (EU) level. In this study, the authors developed a linear regression model to analyze the relationship between business expenditure on research and development (R&D), private investments, gross domestic product (GDP) expenditures on R&D, resource productivity, and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Entrepreneurial opportunity is the formation of new means, new goals, or new means-goals to achieve the possibility of introducing new products, new services, new raw materials, and new ways of an organization [1]. At the same time, from a sustainable perspective, some scholars found that identifying, evaluating, and developing sustainable entrepreneurial opportunities can improve the ecological and social environment, and obtain economic returns while eliminating market failure related to ecological and social problems [23][24][25].…”
Section: Entrepreneurial Opportunities Identificationmentioning
confidence: 99%
“…Entrepreneurial opportunity is the formation of new means, new goals, or new means-goals to achieve the possibility of introducing new products, new services, new raw materials, and new ways of an organization [1]. At the same time, from a sustainable perspective, some scholars found that identifying, evaluating, and developing sustainable entrepreneurial opportunities can improve the ecological and social environment, and obtain economic returns while eliminating market failure related to ecological and social problems [23][24][25].…”
Section: Entrepreneurial Opportunities Identificationmentioning
confidence: 99%
“…Recycled biowaste is expressed in kilograms per capita. This indicator indirectly measured as the ratio of composted/methanized municipal waste (in mass unit) over the total population (in numbers) [64] is part of the Circular Economy indicator set [65] because it monitors the progress made towards a circular economy, from the perspective of waste management [66,67].…”
Section: Methodsmentioning
confidence: 99%
“…Desse modo, inovação e empreendedorismo, caracterizados pelas PMEs estão positivamente relacionados (Banacu et al, 2019) sendo necessário maior compreensão acerca da gestão do termo sustentabilidade, levando em consideração a formulação de políticas que tentam identificar quais seriam as soluções mais proativas e eficazes quando direcionadas aos stakeholders.…”
Section: Elementos Teóricos Da Pesquisaunclassified